Protective effects of esculetin against ovary ischemia–reperfusion injury model in rats - Güvenç, Mehmet; Yüksel, Murat; Kutlu, Tuncer; Etyemez, Muhammed; Gökçek, İshak; Cellat, Mustafa (Wiley, 2023)
AbstractAimsOvarian ischemia–reperfusion (I/R) injury is a phenomenon that necessitates urgent intervention, which occurs as a result of ovarian torsion, and it is frequently seen in young women. A large amount of free radical and oxidative damage as a result of I/R plays a role in the cause of the incident. Antioxidant agents are thought to be beneficial in preventing this damage, and the potential protective effects of esculetin, which had not been tested previously, were investigated in this study.Study DesignThe rats in the study were divided into five groups at random: control, sham, esculetin, I/R, and treatment. Oxidative stress parameters, proinflammatory cytokines, nuclear factor erythroid 2‐related factor 2 (Nrf‐2)/nuclear factor‐kβ (NF‐κβ) pathway, and histopathological analyses were evaluated at the end of the study.Key FindingsAfter I/R, malondialdehyde levels, proinflammatory cytokines, tumor necrosis factor‐α and interleukin‐1β levels and NF‐κβ expressions were increased, Nrf‐2 expression and glutathione level decreased and the histopathologic picture deteriorated. However, as a result of the esculetin treatment, ameliorative effects in the aforementioned parameters were determined, and it was ensured that they returned to normal levels.ConclusionAccording to these findings, esculetin has protective effects on I/R damage by lowering lipid peroxidation and having antioxidant and anti‐inflammatory properties.SignificanceOur results proved the protective effect of esculetin against ovarian IR injury in rats and this may be attributed to Nrf‐2/NF‐κβ axis which showed antioxidant and anti‐inflammatory effects. Therefore, esculetin can be used in the future for preventive effects to ovarian IR injury.
Keywords: Oxidative Stress; Tumor Necrosis Factor-alpha; Reperfusion Injury; Anti-Inflammatory Agents; Humans; Animals; Female; Ovarian Diseases; Umbelliferones; Rats, Wistar; Antioxidants; Rats; 3. Good health